Reliability of the Brazilian version of HCR-20 assessing risk for violence - Borba Telles, Lisieux Elaine de (2009)
Objective: Assessing risk for violence is a complex task often based on not objective or structured clinical evaluations. HCR-20 Assessing Risk for Violence has been used in several countries to increase the accuracy of this exam. The purpose of this study was to inform on central aspects of this instrument, as well as the results of the reliability assessment of the HCR-20 Assessing Risk for Violence in a Brazilian inpatient criminal population. Method: Two examiners independently assessed a random sample of 30 patients that were under criminal commitment at the Mauricio Cardoso Forensic Psychiatric Institute Results: Mean consensus values means were as follows: Historical = 13.1; Clinical = 4.8 and Risk management = 5.8. The value of the Intraclass Correlation Coefficient for the score of subscale Historical was 0.97, for subscale Clinical it was 0.94, and for subscale Risk management, 0.96. As to the individual items of the HCR-20 Assessing Risk for Violence, the result of the Intraclass Correlation Coefficient was good to excellent (mean = 0.97; interval, from 0.60 to 0.99). Conclusion: The interrater reliability of the Brazilian version of the HCR-20 Assessing Risk for Violence scale was similar to the results of studies in other countries.